The ArcB leucine zipper domain is required for proper ArcB signaling. - Luis Alberto Nuñez Oreza; Adrián F Alvarez; Imilla I Arias-Olguín; Alfredo Torres Larios; Dimitris Georgellis (PLoS ONE, 2012)
The Arc two-component system modulates the expression of numerous genes in response to respiratory growth conditions. This system comprises ArcA as the response regulator and ArcB as the sensor kinase. ArcB is a tripartite histidine kinase whose activity is regulated by the oxidation of two cytosol-located redox-active cysteine residues that participate in intermolecular disulfide bond formation. Here, we report that the ArcB protein segment covering residues 70-121, fulfills the molecular characteristics of a leucine zipper containing coiled coil structure. Also, mutational analyses of this segment reveal three different phenotypical effects to be distributed along the coiled coil structure of ArcB, demonstrating that this motif is essential for proper ArcB signaling.